Some Reflections on Ethnic Issues in Uzbekistan in the XX Century (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses the policy of the former Soviet Union in Central Asia in the twentieth century, especially in Uzbekistan, its impact on the understanding and unification of the peoples of the region, and the factors that led to the formation of the Uzbek people as a nation